HAK ASASI MANUSIA DAN PERLINDUNGAN LINGKUNGAN HIDUP - Priya Tandirerung Pasapan (Paulus Law Journal, 2020)
Attention to environmental issues is not only limited to local or national problems but also as an international problem. Protection of the environment has become a main agenda of the international community. This program based on the reality of various environmental pollution and damage events that have had a profound impact on human life. This article analyzes the relationship between the environment and human rights and the Indonesian government's policy to protect the environment. The purposes of this paper are to find out the correlation between human rights and the environment, and find out the policies of the Indonesian government in this regard. Through this article, it can be seen that the environment is an inherent part of human rights, which the right to a good and healthy environment is a human right. Furthermore, the Indonesian government has also taken steps and efforts in ensuring environmental protection, one of which is through legal instruments of the law.